A giant radio halo in a low-mass SZ-selected galaxy cluster: ACT-CL J0256.5+0006 - Knowles, K.; Intema, Hubertus; Baker, A.; Bharadwaj, V.; Bond, J.; Cress, C.; Gupta, N.; Hajian, A.; Hilton, M.; Hincks, A.; Hlozek, R.; Hughes, J.; et al. (Oxford University Press, 2016)
We present the detection of a giant radio halo (GRH) in the Sunyaev-Zel'dovich (SZ)-selected merging galaxy cluster ACT-CL J0256.5+0006 (z = 0.363), observed with the Giant Metrewave Radio Telescope at 325 and 610 MHz. We find this cluster to host a faint (S610= 5.6 ± 1.4 mJy) radio halo with an angular extent of 2.6 arcmin, corresponding to 0.8 Mpc at the cluster redshift, qualifying it as a GRH. J0256 is one of the lowest mass systems, M500, SZ= (5.0 ± 1.2) × 1014M?, found to host a GRH. We measure the GRH at lower significance at 325 MHz (S325= 10.3 ± 5.3 mJy), obtaining a spectral index measurement of a325610= 1.0-0.9+0.7. This result is consistent with the mean spectral index of the population of typical radio haloes, a = 1.2 ± 0.2. Adopting the latter value, we determine a 1.4 GHz radio power of P1.4 GHz= (1.0 ± 0.3) × 1024W Hz-1, placing this cluster within the scatter of known scaling relations. Various lines of evidence, including the intracluster medium morphology, suggest that ACT-CL J0256.5+0006 is composed of two subclusters. We determine a merger mass ratio of 7:4, and a line-of-sight velocity difference of v? = 1880 ± 210 km s-1. We construct a simple merger model to infer relevant time-scales in the merger. From its location on the P1.4 GHz-LXscaling relation, we infer that we observe ACT-CL J0256.5+0006 just before first core crossing.